Relationship of abstract reasoning and language ability to comprehension difficulties in mathematics - Juta, Teresa O.
This study determined the extent of the relationships between abstract reasoning, language ability, and mathematical comprehension. Three tests were used to measure the relationships between these variables. The first was a mathematical comprehension test constructed by the researcher; the second measures the reading aspect; and the third was an abstract reasoning test constructed by the U.P.-S.E.C. Research and Evaluation Department.